An OT and PT Explore SoTL: Our Journey Towards Strengthening, Expanding, and Scaffolding Anti-Oppressive Pedagogy in a School of Rehabilitation Science - Oosman, Sarah N.; Stavness, Carrie L. (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2024)
Physical therapy (PT) students and graduates in Saskatchewan, Canada, are entering a health system requiring enhanced cultural humility, social justice, self-decolonization, and anti-oppressive practice skills. In this reflective essay, we describe our exploration of the complexities of the Scholarship of Teaching and Learning (SoTL), which provide insight into our current and evolving teaching and learning practices in a Master of Physical Therapy (MPT) academic program. Applying SoTL to our MPT pedagogy provides a rigorous, evidence-informed research approach impacting social-justice learning outcomes among PT learners, but we emphasize that it is more than the outcomes that give SoTL its strength. SoTL is also a process that strengthens relationships, builds a culture of collective leadership grounded in relational accountability and humility, lays the foundation for equitable engagement with students as partners, requires reflection and introspection, and could arguably itself be considered a social justice intervention.